First and second line drug resistance among treatment naïve pulmonary tuberculosis patients in a district under Revised National Tuberculosis Control Programme (RNTCP) in New Delhi - Vithal Prasad Myneedu; Ritu Singhal; Khalid Umer Khayyam; Prem Prakash Sharma; Manpreet Bhalla; Digamber Behera; Rohit Sarin (Springer, 2019)
There is limited information of level of drug resistance to first-line and second line anti-tuberculosis agents in treatment naïve pulmonary tuberculosis (PTB) patients from the Indian region. Therefore, the present prospective study was conducted to determine the antimicrobial susceptibility to first-line and second line anti-TB drug resistance in such patients. Sputum samples from consecutive treatment naïve PTB cases registered in Lala Ram Sarup (LRS) district, under RNTCP containing 12 Directly Observed Treatment Centre's (DOTS), were enrolled using cluster sampling technology. A total of 453 samples were received from July 2011 to June 2012. All samples were cultured on solid medium followed by drug susceptibility to first and second line anti-tubercular drugs as per RNTCP guidelines. Primary multi-drug resistance (MDR) was found to be 18/453; (4.0%). Extensively drug resistance (XDR) was found in one strain (0.2%), which was found to be resistant to other antibiotics. Data of drug resistant tuberculosis among treatment naïve TB patients are lacking in India. The presence of XDR-TB and high MDR-TB in small population studied, calls for conducting systematic multi-centric surveillance across the country.